USING LOGISTIC METHODS AND MODELS IN THE SYSTEM OF MATERIAL-TECHNICAL PROVISION OF RAILWAY TRANSPORT - Kostiuchenko, L. (Science and Transport Progress, 2006)
The article presents the studies dealing with uses of logistic methods and models in the resource supply management of railway transport and enlists the principles of use of graphic method in determining the nomenclature groups.